M KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KOMPETENSI GURU DI SMK KABUPATEN INDRALAYA UTARA - Imron, Imron; Ahyani, Nur; Kesumawati, Nila (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
The purpose of this study was to describe the principal's leadership in improving teacher competence. This study was conducted at SMK in North Indralaya Regency. The method used in the study was a qualitative method. Data collection techniques used observation, interviews, and documentation. Data were analyzed using qualitative techniques. The results of this study indicate that efforts to improve teacher competence through various activities that include pedagogical, personality, social, and professional competence. Teachers actively participate in training, utilize ICT, and discuss to improve learning. Educators are encouraged to be role models and establish good relationships with parents of students and the community. Teachers continue to improve their mastery of ICT materials and skills. The principal plays an important role as an educator, manager, administrator, supervisor, leader, innovator, and motivator. The principal shows commitment to the curriculum, provides opportunities for teacher development, ensures the implementation of educational standards, supervises, becomes a role model, encourages the use of ICT, and requires participation in MGMP for all teachers.